Вплив анізометричних наповнювачів на електричні властивості нанокомпозитів на основі поліпропіленгліколю - Lysenkov, E.A.; Klepko, V.V. (Publishing house "Academperiodika", 2022)
Electrical properties of polypropylene glycol-based nanocomposites have been studied using the impedance spectroscopy method. The application of the Miyamoto–Shibayama equation enabled the contributions of the activation and nonactivation mechanisms of charge transfer in the systems filled with laponite to be separated. The critical temperature of a mechanism change was determined. Using the equivalent circuit method and the Macdonald theory, two types ofconductivity, ionic and electronic, are found in nanocomposites filled with carbon nanotubes.